1988
DOI: 10.1209/0295-5075/5/5/011
|View full text |Cite
|
Sign up to set email alerts
|

Surface Carbonate on Ag{110}: an X-Ray Absorption Fine-Structure Study

Abstract: The surface carbonate species formed by the reaction of CO2 with preadsorbed oxygen on Ag{ l l O } has been studied with X-ray photoabsorption techniques. The analysis of the oxygen and carbon K near edge structure (NEXAFS) shows that the molecule is adsorbed flat on the surface and that, at least for the 0-resonances, the effective symmetry remains D3h. The observed (1 x 2) surface structure thus results from an adsorbate-induced reconstruction. The analysis of the extended fine structure (SEXAFS) gives an O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…This proved surprisingly sensitive to the azimuthal orientation of the molecule, but is not very sensitive to the tilt. Interestingly, earlier NEXAFS studies 54,55 had also indicated that the molecular plane is parallel to the surface, but with an estimated precision of only AE151. As may be seen in Fig.…”
Section: Other Carboxylate Alkoxy and Related Studiesmentioning
confidence: 99%
“…This proved surprisingly sensitive to the azimuthal orientation of the molecule, but is not very sensitive to the tilt. Interestingly, earlier NEXAFS studies 54,55 had also indicated that the molecular plane is parallel to the surface, but with an estimated precision of only AE151. As may be seen in Fig.…”
Section: Other Carboxylate Alkoxy and Related Studiesmentioning
confidence: 99%
“…Two other dominating features are also found in all compounds at 285 eV and around 288.6 eV, although the relative intensity of the three peaks varies. The assignment of the features in the absorption spectra can be done in terms of the building block model, 24,25 and by comparison with published absorption spectra of various carbonates 26,27,24 and molecular orbital (MO) calculations. 28,29 The feature at 290.3 eV can be attributed to C1sp* transitions (C 2p-O 2p derived orbitals).…”
Section: X-ray Absorptionmentioning
confidence: 99%
“…Until very recently, NEXAFS studies of the carbonate system were restricted to gaseous CO 2 [26], and to carbonates adsorbed to a surface [27] or in various solid mineral forms [28] by the difficulties then inherent in addressing liquid samples by this high vacuum technology. In 2011, we reported the first NEXAFS study of aqueous carbonate and bicarbonate ions [22], which was followed by an X-ray emission study in 2014 [29].…”
Section: Introductionmentioning
confidence: 99%